Sinergetsko snovanje novega zgostitvenega središča Ilovica v južnem delu Ljubljane - Šašek-Divjak, Mojca (Urbani izziv, 2005)
The article presents the comprehenisve approach to planning of the new, sustainably-designed housing estate Ilovica in southern Ljubljana. It was executed as an ideal model of a larger densely populated settlement, which would also ensure the reconstruction of the extant area of low-density housingwith deficient utilities provision. Besides the architectural and urbanistic design and solutions to technological problems, we also showed implementation possibilities that use instruments of real estate polices (re-parceling etc.) and prepared a feasability study of the investment. Such multi-faceted projects demand multi-disciplinary approaches, whereby only the full partcipation of various experts and also wider community can lead to better results with synergetic effects that are the result of common endeavour.
Keywords: Ilovica; Ljubljana; mestni predeli; prostorsko urejanje; stanovanjska naselja; urbani prostor; urbanistična ureditev